Usury-Free Capital through Sharia Fintech: Insights from Hanafi, Maliki, al-Shafi'i, and Hanbali Madhhabs - Syarif, Muhammad Fazlurrahman; Aysan, Ahmet Faruk (Mazahibuna: Jurnal Perbandingan Mazhab, 2024)
Sharia fintech (Financial Technology) is an important alternative to overcome the problem of usury prohibited by Islamic law. Therefore, this study aimed to analyze Sharia fintech as a solution for capital without usury based on the perspectives of four madhhabs, namely Hanafi, Maliki, al-Shafi'i, and Hanbali. A qualitative study was conducted with a comparative Islamic law method. Empirical data were collected from classical fiqh literature and contemporary studies related to fintech and usury. The collected data were analyzed through the stages of reduction, presentation, editing, and drawing conclusions from tracing the suitability of Sharia fintech with the principles held by each school. The results showed that there was significant difference between the four schools in interpreting whether Sharia fintech was truly free from usury. The Hanafi and Hanbali madhhabs were more careful in accepting the Sharia fintech model because of the potential for hidden usury elements. However, the Maliki and al-Shafi'i madhhabs were more open, provided that fintech contracts adhere to Sharia principles. The originality of this study was in the comprehensive and simultaneous analysis of the four madhhabs perspectives, which has not been widely investigated in the context of Sharia fintech. The implications of this study include the importance of stricter regulation to ensure full compliance with Sharia principles. Furthermore, this study contributed to financial institutions and regulators in developing Sharia fintech products that were more inclusive and in accordance with the provisions of various madhhabs. More opportunities were also opened for further studies on the implementation of Sharia fintech in multiple countries with different madhhab backgrounds.